Talent Management in Improving The Employees Performance of PT PLN (Persero) TJBB APP Cawang - Asri Nur Mutiara; Aida Vitayala Hubeis; Anggraini Sukmawati (School of Business, IPB University (SB-IPB), 2019)
Human resources are the key to the company's success in achieving company's goals. One of the things that affect the performance of employee is the employee’s talent. PT PLN (Persero) is a company that implements talent management to manage human resource in order to achieve maximum performance. This study aims to analyze the implementation of talent management, to analyze its impact in improving the employee’s performance, and to formulate the implementation of managerial implications for the employee development of PT PLN (Persero) APP Cawang. This research was conducted using a questionnaire towards 68 employees of first-line and middle management at PT PLN (Persero) APP Cawang. The data was analyzed using Structural Equation Modelling - Partial Least Squares (SEM-PLS). The conclusion of this study is the company should provide some development programs for talented employees to improve their performance. The results show that there is a significant relationship between talent management variables and the employee’s performance in PT PLN (Persero) TJBB APP Cawang. Talent management is very influential on employee performance in PT PLN (Persero) TJBB APP Cawang, which is 38.2% and the remaining 61.8% is influenced by other factors.Keywords: state-owned enterprises (BUMN), first-line management, middle management, employee performance, SEM, talent management